DNA barcoding and antioxidant activity of Fritillaria karelinii (Fisch. ex D. Don) Baker from nature habitats of southeast Kazakhstan - A. Tursynbay; S. Jo; Z.Z. Karzhaubekova; N.G. Gemejiyeva; J.-H. Paik; A.G. Sankaybaeva; G.S. Mukan (All Life)
The molecular phylogeny of Kazakhstan’s Fritillaria karelinii (Fisch. ex D. Don) Baker was reconstructed and analyzed to confirm its genetic identification and phylogenetic position. The BLAST results were matched at a high rate of 98%, and (nrITS and rbcL) formed a single clade in the phylogenetic analysis. The studied plant belongs to the branch of the subgenus Fritillaria Tourn. ex L., which is consistent with the literature. This confirmed a clear genetic identification and taxonomic position of the studied plant. Despite some sequence differences between the Kazakhstani and Chinese species (C1, C3, C5) found in the nrITS region, no specific sequence existed for the other markers (rbcL and trnH-psbA). The outcomes of the antioxidant activity of F. karelinii fractions were prepared by extraction with 70% ethanol and separation into several fractions using the partition procedure with chloroform, ethyl acetate, n-butanol, and water. Among these, the ethyl acetate fraction most significantly affected the activity in the FC, DPPH, and FRAP assays.